The silent scream: Domestic violence in Malaysia - Abdul Ghani, Mariny; Ahmad, Noor Azizah; Tewiran, Syaliza Adiha (2014)
This paper offers some reflections on coming to terms with the situation of domestic violence in Malaysia.The issue of domestic violence has been identified across all religions, ethnicities, cultures, ages and economic statuses.Indeed, it also describes as a significant social and public health problem in many countries in the world. The common definition of domestic violence is often referred to as the violence occurred between husband and wife, non-married partners (dating as well as cohabitation) and among the same sex relationships.In Malaysia, however, the explanation of domestic violence situation is only regarded as the violence occurring among intimate partners who are either spouses or ex-spouse of a legal relationship.Since the ratification of the United Nations Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) in 1970, the government has established numerous plans and developed various strategies in order to assist domestic violence victims and survivors in Malaysia.Therefore, this paper seeks to critically review the recent scenario of the problem particularly to describe the magnitude of domestic violence against women in Malaysia as well as to identify limitations in combating this social problem in the country.